Adrenocortical neoplasms in children: Treatment and outcomes - Vishesh Jain; Mehak Sehgal; Anjan Dhua; Sameer Bakhshi; Devasenathipathy Kandasamy; Kalaivani Mani; Rajni Sharma; Vandana Jain; Nikhil Tandon; Sandeep Agarwala (Journal of Indian Association of Pediatric Surgeons, 2022)
Background: Adrenocortical tumors are rare tumors in children with a paucity of outcome data, especially in a resource-challenged setting. Materials and Methods: A retrospective study was conducted to evaluate the presentation, management, and outcomes of children with adrenocortical tumors who presented to our institute from January 1992 to December 2019. Results: During the study period, 28 children were included. Adenoma was present in nine children and the remaining 19 children had adrenocortical carcinoma. The median age of presentation was 48 months. Nearly half of the children with carcinomas presented with a mass compared to only 10% adenomas (P = 0.049). Virilization was present in 60% of the patients and in most cases was associated with Cushingoid features. Three children (15.7%) had metastasis at presentation. All children underwent surgical excision with a spill in 6 and gross residue in two patients. Recurrence was observed in five patients after a mean duration of 11.8 months. The 4-year overall survival and event-free survival were 100% in patients with adenomas compared to 75% and 44%, respectively, in carcinoma. Children who underwent complete surgical excision without any spill had a relatively favorable outcome. Conclusion: Adrenocortical tumors are uncommon tumors in children. Adenomas have a favorable outcome. There was no disease-free survival in incompletely resected or metastatic tumors. Tumor spill may also have an adverse outcome in completely resected tumors.